Hasil Belajar Pendidikan Jasmani dan Olahraga Siswa Sekolah Dasar: Pengaruh Keterampilan Motorik (Tinggi) dan Model Pembelajaran (Kooperatif) - Setiawan, Anang; Yudiana, Yunyun; Ugelta, Surdiniaty; Oktriani, Seni; Budi, Didik Rilastiyo; Listiandi, Arfin Deri (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
The level of motor skills of elementary school students can be influenced by many things such as movement experience, the environment, and facilities for learning so that it also impacts on learning outcomes. This study intends to find out the differences in physical education and sports learning outcomes of floor gymnastic material from elementary school students who have high motor skills. Floor gymnastic learning material is used in two cooperative learning model strategies (Student Teams Achievement Divisions and Jigsaw). The research approach method used was an experiment with a Pre-Experimental design. The students' motor skills were measured using the Johnson Fundamental Skills Test, while the series of floor motion exercises for Grade V Elementary School students were used as research instruments. The results of his study showed that there were differences in physical education learning outcomes and sports materials on floor gymnastics, groups of students with the STAD strategy got better learning outcomes compared to the Jigsaw strategy group. So, it can be concluded that the use of the STAD strategy cooperative learning model for students with high motor skills gives a better influence than Jigsaw's strategy on learning outcomes of physical education and sports learning exercises for floor gymnastics.AbstrakTingkat keterampilan motorik siswa Sekolah Dasar bisa dipengaruhi oleh banyak hal seperti pengalaman gerak, lingkungan, serta fasilitas untuk pembelajaran sehingga berdampak pula terhadap hasil belajarnya. Penelitian ini bermaksud untuk mengetahui perbedaan hasil belajar pendidikan jasmani dan olahraga materi senam lantai dari siswa Sekolah Dasar yang memiliki keterampilan motorik tinggi. Materi pembelajaran senam lantai digunakan pada dua strategi model pembelajaran kooperatif (student Teams Achievement Divisions dan Jigsaw). Metode Pendekatan penelitian yang digunakan adalah eksperimen dengan desain Pre-Experimental. Keterampilan motorik siswa diukur menggunakan Johnson Fundamental Skills Test, sedangkan rangkaian gerak senam lantai untuk siswa Sekolah Dasar kelas V digunakan sebagai instrumen penelitian. Hasil penelitiannya menunjukkan bahwa terdapat perbedaan hasil belajar pendidikan jasmani dan olahraga materi senam lantai, kelompok siswa dengan strategi STAD mendapatkan hasil belajar yang lebih baik dibandingkan dengan kelompok strategi Jigsaw. Sehingga, dapat ditarik kesimpulan bahwa penggunaan model pembelajaran kooperatif strategi STAD kepada siswa dengan keterampilan motorik tinggi memberikan pengaruh yang lebih baik daripada strategi Jigsaw terhadap hasil belajar pendidikan jasmani dan olahraga materi pembelajaran senam lantai.